Belajar Bisnis Seru dengan Praktik Langsung Game Jack’s Milyarder - Anita Tarihoran; Evi Juita Wailan’An; Yola Yolanda; Sulia Sulia; Sonya Enda Natasha S. Pandia (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
The purpose of this activity is to improve students' understanding and interest in the business world through contextual and interesting methods. In addition, this program also aims to provide alternative models of entrepreneurship learning that can be used by teachers in classroom learning activities on an ongoing basis. This community service activity will be carried out through a participatory and educational approach that is designed in stages to suit the level of understanding of high school students. The method of implementing the activity consists of initial socialization and coordination activities, basic business and entrepreneurship training, Jack's Billionaire game simulation, reflective discussion and learning evaluation, monitoring and mentoring after the activity. The overall activity continued to run well and smoothly. The students remained enthusiastic in participating in each session, from training to educational games. The community service team was also pleased because the main objective of this activity could be achieved, namely to improve students' understanding and interest in the business world and entrepreneurship through fun methods.Abstract also written in English containing key issues, objectives, methods and results of implications.